Manifestations in nature of self-controlled quasi-stationary nuclear fusion into magnetized low-temperature hydrogen plasma - Vysotskii, Vladimir; Vysotskyy, Mykhaylo (Frontiers in Materials, 2024)
This paper examines the characteristics of nuclear reactions occurring in low-temperature magnetized deuterium plasma. It is demonstrated that considering the ionization-recombination dynamics of deuterium atoms in this plasma allows for the potential realization of efficient nuclear fusion at low thermal energies kT≈10−20 eV. The study shows that these processes are linked to the formation of coherent correlated states of deuterons, accompanied by the generation of giant energy fluctuations δE≥10−50 keV during each recurring ionization event of deuterium atoms. These findings align with known anomalies in the solar atmosphere, such as the sharp temperature increase above the Sun’s surface and the observed excess concentration of helium-3 ions in the solar wind. Furthermore, this process may explain well-documented experimental results, such as neutron generation during electric discharges in gas.